Container-Based Sanitation Services and Attrition: An Examination of Drivers and Implications - VanRiper, Froggi; Russel, Kory C.; Cramer, Lori A.; Tillias, Daniel; Laporte, Jessica; Lloyd, Erica; Kramer, Sasha (Frontiers in Environmental Science, 2022)
Haiti is far from achieving the UN goal of sanitation access for all; 20% of the population has no sanitation access, and less than 0.1% of the country’s excreta is safely managed. Container-Based Sanitation (CBS) may be key to achieving timely and equitable sanitation coverage in Haiti’s cities. CBS can provide immediate sanitation access without preexisting infrastructure, and where permanent infrastructure is impractical. Investor caution and policy barriers, however, presently limit the growth of CBS solutions. Globally, most CBS services are provided by private organizations like EkoLakay, which provides a portable toilet and weekly excreta collection for a monthly fee. While the EkoLakay service is popular, attrition is high. This study examines the relationship between users and the service, and its role in improved sanitation accessibility. For this study, 633 active and former EkoLakay subscribers in Cap Haïtien were interviewed to reveal causes and implications of attrition. Households with active EkoLakay subscriptions are more likely than former subscribers to live in unauthorized informal residences and to lack energy or water infrastructure. A quarter of users unsubscribe voluntarily, after investing in permanent sanitation infrastructure. Over 30% of former users, however, reported unsubscribing due to economic challenges. Many involuntary terminations resulted in households losing access to private improved sanitation or reverting to open defecation, reducing progress toward global sustainability goals. Insights obtained contextualize the relationship between users and CBS services to inform public strategies for mitigating barriers to achieving universal safe sanitation